High-level methodologies for grammar engineering, introduction to the special issue - Duchier, Denys; Parmentier, Yannick (Journal of Language Modelling, 2015)
Grammar Engineering is the task of designing and implementing linguistically motivated electronic descriptions of natural language (so-called grammars). These grammars are expressed within well-defined theoretical frameworks, and offer a fine-grained description of natural language. While grammars were first used to describe syntax, that is to say, the relations between constituents in a sentence, they often go beyond syntax and include semantic information. Grammar engineering provides precise descriptions which can be used for natural language understanding and generation, making these valuable resources for various natural language applications, including textual entailment, dialogue systems, or machine translation. The first attempts at designing large-scale resource grammars were costly because of the complexity of the task (Erbach et al. 1990) and of the number of persons that were needed (see e.g. Doran et al. 1997). Advances in the field have led to the development of environments for semi-automatic grammar engineering, borrowing ideas from compilation (grammar engineering is compared with software development) and machine learning. This special issue reports on new trends in the field, where grammar engineering benefits from elaborate high-level methodologies and techniques, dealing with various issues (both theoretical and practical).